A Rotor Position and Speed Observer for Permanent Magnet Motor with Non Sinusoidal EMF Waveform - de Angelo, Cristian Hernan (2005)
A new nonlinear reduced-order observer to estimate the rotor speed and position for permanent-magnet motors, with arbitrary electromotive force (EMF) waveform, is presented. The proposed observer is suitable for the realization of a torque control with minimum torque ripple. In order to implement the observer, the EMF generated by the motor is first obtained experimentally offline. After that, it is approximated by a Fourier series in order to develop the model to be used in the online estimation. From the estimated EMF, rotor position and speed are calculated using the relationship between the EMF and the rotor variables. The proposal is validated with experimental results.